ANALISIS KEMAMPUAN PEMAHAMAN KONSEP PADA MATERI BILANGAN BULAT DITINJAU DARI GENDER PADA SISWA KELAS VII SMP NEGERI 2 GALANG - Satriana, Satriana; Sukayasa, Sukayasa; Sugita, Gandung (Jurnal Elektronik Pendidikan Matematika Tadulako, 2022)
This study aims to obtain a description of the ability to understand concepts in the matter of integers in terms of gender in class VII students of SMP Negeri 2 Galang. This type of research is qualitative research. The subjects of this study were students of class VIII B of SMP Negeri 2 Galang in terms of gender. Data were collected through written tests and interviews. Researchers triangulated time to test the credibility of the data. Based on the results of the written test and interview results, the results of this study showed that the subjects were male and female who had moderate ability. The results of this study (1) Subjects with moderate mathematical ability, on the indicators of classifying objects according to certain properties, in part a are able to classify quite well, in part b are less able to classify based on the properties of integers. In indicators of using, utilizing, and selecting certain procedures or operations, being able to use procedures well, on indicators of applying concepts or problem solving algorithms, not yet fully able to understand concepts. (2) Subjects with moderate mathematical ability on the indicator classify objects according to certain properties in part a that have not been able to classify well, in part b they are able to classify based on the properties of integers quite well. On indicators of using, utilizing, and selecting certain procedures or operations, not being able to use procedures properly, on indicators of applying concepts or problemsolving algorithms, not yet fully able to understand concepts.